The retreat from marriage and parenthood : examining the causes and consequences of declining rates (Contemporary perspectives on family research ;, 2025)
Around the globe, two of the more fundamental attributes of families and households have been changing, as both rates of marriage and fertility have been steadily decreasing. These declines have numerous associated causes - among them, increases in singlehood, increases in cohabitation, and greater emphases upon individualism and materialism. The Retreat from Marriage and Parenthood seeks a broad examination of the retreat from marriage and parenthood. Featuring diverse theoretical and methodological chapters exploring the many issues pertaining to these seismic changes, the authors chronicle the many dramatic impacts from shifts in attitudes to marriage and family. The chapters include discussion of pressing issues such as increasing ages at marriage, singlehood, cohabitation and alternative forms of intimate relationships, the impact of financial stress upon marriage and fertility, consequences of changing age structures, racial and ethnic variations in marriage and parenthood rates, changing meanings of family lineage, the impact of marriage and fertility declines upon other social institutions, and gender differences in the appeal of marriage and parenthood. Acknowledging the reality of these shifts in marriage and fertility rates, and that they warrant greater attention by researchers, this is an insightful edited collection for scholars of family research.